THE DEVELOPMENT OF MAGNETIC FIELD LEARNING MODULE INTEGRATED WITH AUGMENTED REALITY (AR) FOR SENIOR HIGH SCHOOL: A NEED ANALYSIS - haris, venny; alias, siti nursaila; Ayop, Shahrul Kadri (UIN Sunan Gunung Djati Bandung, 2025)
The aim of this study was to provide empirical data for the development of an augmented reality (AR) integrated physics learning module that focuses on difficult topics among high school students. Using a quantitative approach, 131 students and 26 physics teachers from West Sumatra completed a needs assessment questionnaire. Magnetic fields were identified as the most difficult topic, cited by 34% of students and 65% of teachers due to their abstract nature and lack of visualization tools. Current teaching methods and materials do not adequately support students' understanding. Both teachers and students expressed a strong preference for modules that integrate AR to visualize abstract concepts, increase engagement, and provide clear explanations, practical activities, and problem-solving examples. Although the potential of AR is recognized, it is underutilized as there is currently no integration with physics modules. This study highlights the urgent need for AR-based modules to improve learning outcomes, especially on complex topics such as magnetic fields.